DESCRIPTION OF ELEGIAC MOOD IN MODERN UZBEK POETRY (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This comprehensive study examines the manifestation and evolution of elegiac moods in modern Uzbek poetry, focusing on works from the late 20th to early 21st century. Through systematic analysis of poetic texts, their contextual significance, and historical development, this research identifies key patterns in how contemporary Uzbek poets express melancholy, loss, and reflection. The study employs multiple methodological approaches, including qualitative textual analysis, comparative literary methods, and historical-biographical analysis to explore the unique characteristics of elegiac expression in Uzbek poetry and its relationship to broader cultural and social contexts. The findings reveal complex patterns of traditional preservation and modern innovation in elegiac expression, contributing to our understanding of contemporary Uzbek literary development.